A cross-sectional evaluation of opt-in testing for sexually transmitted and blood-borne infections in three Canadian provincial correctional facilities: a missed opportunity for public health?. Issue 3 (31st May 2019) - Gratrix, Jennifer; Smyczek, Petra; Bertholet, Lindsay; Lee, M.C.; Pyne, Diane; Woods, Dan; Courtney, Keith; Ahmed, Rabia
Abstract : Purpose: Incarceration provides an opportunity for screening and treatment of sexually transmitted and blood-borne infections (STBBIs) in high-risk groups. The purpose of this paper is to determine positivity rates of STBBI screening within correctional facilities using opt-in strategies and estimate the proportion of admissions tested. Design/methodology/approach: A cross-sectional, retrospective review of testing data from January 2012 to August 2015 from three provincial correctional facilities located in Alberta, Canada was completed. Analysis variables included STBBI, gender, facility, collection year and age. STBBI-stratified analysis was performed to identify correlates for positivity using univariate and logistic regressions. Findings: Overall prevalence of chlamydia was 11.2 percent and gonorrhea was 3.5 percent; correlates for both were younger age and facility type. The syphilis prevalence rate was 3.2 percent; correlates included being female, older age, adult facilities, with later years being protective. In total, 14 (0.3 percent) newly diagnosed HIV cases were found, prevalence increased with age. HBV prevalence was 1.7 percent with no significant correlations. Nearly one-tenth ( n =422) of those screened for HCV antibody were positive; all variables were significantly correlated. Overall estimates of the proportion of admissions tested by STBBI were low and ranged from 4.8 to 16.1 percent. Originality/value: This study found high rates of STBBI in correctional facilities and showed that only a small proportion of the population was tested using an opt-in strategy. Shifting to an "opt-out" strategy may be warranted.